PERANCANGAN FORUM DISKUSI UNIVERSITAS SURYADARMA BERBASIS WEBSITE DAN APLIKASI ANDROID - Yulisa Gardenia; Aziz Hardaya (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
This time, development of technolgy and informastion is very fast, All fields of activity in the development must be equipped with updated technology including association (Forum) in university, precisely at the Air Force University of Marsekal Suryadarma. Forum is the information media, which provides convenience in presenting information or discussion in The Air Force University of Marsekal Suryadarma. One of the technologies used in creating the Air Force Marsekal Suryadarma University Forum is the Laravel Framework and the Andorid Application using Android Studio.Laravel Framework is a PHP framework that has been tested by many people, and I also quite understand well about this framework so i use Laravel framework for created The Air Force Marsekal Suryadarma University Forum. The Android Apps of The Air Force Marsekal Suryadarma University Forum can help us to access this situs from android smartphone , so this apps its very user friendly and we can access every where with smartphone apps or website. Â Keywords: Association, Air Force University of Marsekal Suryadarma, Website, Android, PHP, Framework, Laravel.